2019
DOI: 10.3389/fpsyt.2019.00776
|View full text |Cite
|
Sign up to set email alerts
|

Bias Toward Drug-Related Stimuli Is Affected by Loading Working Memory in Abstinent Ex-Methamphetamine Users

Abstract: Background: There is a trade-off between drug-related impulsive process and cognitive reflective process among ex-drug abusers. The present study aimed to investigate the impulsive effects of methamphetamine-related stimuli on working memory (WM) performance by manipulating WM load in abstinent ex-methamphetamine users.Methods: Thirty abstinent ex-methamphetamine users and 30 nonaddict matched control participants were recruited in this study. We used a modified Sternberg task in which participants were instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…In relation to the improvement of executive component of updating, the results of the present work are consistent with previous studies in which improvements in working memory are reported after the completion of a specialized rehabilitation program ( 2 , 7 , 11 , 50 , 51 ). Different studies show that the specific work of working memory is a facilitator of cognitive functions such as learning, verbal comprehension, thinking, reasoning or decision-making and a generator of an efficient buffering effect against attentional bias toward salient stimuli related to substance use ( 52 , 53 ). Similar results to those obtained in the present study have been found in other populations with psychiatric pathologies ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the improvement of executive component of updating, the results of the present work are consistent with previous studies in which improvements in working memory are reported after the completion of a specialized rehabilitation program ( 2 , 7 , 11 , 50 , 51 ). Different studies show that the specific work of working memory is a facilitator of cognitive functions such as learning, verbal comprehension, thinking, reasoning or decision-making and a generator of an efficient buffering effect against attentional bias toward salient stimuli related to substance use ( 52 , 53 ). Similar results to those obtained in the present study have been found in other populations with psychiatric pathologies ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 For individuals with SUD, some studies suggested that addiction-related cues-induced attention/eye movement capture is fully automated and independent of cognitive factors such as the top-down goal, similar to stimulus-driven attention capture. 1 As drug 14 and negative emotional cues 10 can catch attention more quickly and automatically, attentional bias in individuals with MUD may be caused by bottom-up processing, specifically, attention orientation. However, some researchers assumed that under certain addiction-related conditions, the attention capture of the reward connection is not completely automatic and is regulated by top-down attention.…”
Section: Introductionmentioning
confidence: 99%